2020
DOI: 10.1111/dth.13718
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐gamma serum level and immunohistochemical expression of CD8 cells in tissue biopsies in patients with alopecia areata in correlation with trichoscopic findings

Abstract: Alopecia areata (AA) is an autoimmune form of nonscarring hair loss. The aim of the study was to assess the serum concentration of interferon gamma (IFN‐γ) and CD8 cell expression in lesional skin biopsies in correlation with the disease severity, activity, duration, and trichoscopic findings in patients with AA. The study included 30 patients with AA and 15 age‐ and sex‐matched healthy controls. Trichoscopy was performed and photographs were captured for the alopecic areas, and the enzyme‐linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…3C). These alterations between the phases correlated with the clinical observations that the Tc1 cell percentages among PBMCs were higher in the chronic phase and that Tc1 cells infiltrated hair follicles in both the acute and chronic phase [27], finally, that the serum IFN-g levels correlated with AA activity and disease duration [28]. These data suggest a systemically-enhanced cytotoxic activity but also a CTL localization in the lesions in acute-AA mice, and in the non-lesions as well as the lesions in chronic-AA mice.…”
Section: Discussionsupporting
confidence: 78%
“…3C). These alterations between the phases correlated with the clinical observations that the Tc1 cell percentages among PBMCs were higher in the chronic phase and that Tc1 cells infiltrated hair follicles in both the acute and chronic phase [27], finally, that the serum IFN-g levels correlated with AA activity and disease duration [28]. These data suggest a systemically-enhanced cytotoxic activity but also a CTL localization in the lesions in acute-AA mice, and in the non-lesions as well as the lesions in chronic-AA mice.…”
Section: Discussionsupporting
confidence: 78%
“…There is a spectrum of inflammatory skin diseases that are characterized by strong upregulation of IFN and recruitment of effector T cells ( 83 , 84 ). This spectrum includes, but is not limited to, CLE ( 85 ), LP ( 86 , 87 ), vitiligo ( 88 ) and AA ( 89 91 ), which are considered autoimmune diseases ( 92 94 ). These diseases come along with a predisposing genetic background, particularly gene polymorphisms of components of the innate and adaptive immune system.…”
Section: Role Of Inflammasomes In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…CXCL chemokines are known to recruit CXCR3+ effector T cells, which accumulate around hair bulbs and exhibit autoreactivity to follicular epithelial cells. These inflammatory events lead to loss of hair follicle immune privilege with anagen arrest ( 89 91 , 100 , 173 , 174 ).…”
Section: Role Of Inflammasomes In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…8 A study including 30 patients with AA and 15 matched controls indicated that serum interferon (IFN)γ levels were significantly higher in patients than in controls and were significantly correlated with disease activity status and duration. 9 A study including 65 patients with AA and 71 healthy controls demonstrated that serum levels of adiponectin were significantly lower in patients with AA than in controls and were negatively correlated with the SALT score. 10 In a study that included 42 patients with AA and 17 control subjects, serum levels of lipocalin-2, insulin, C-peptide, and homeostasis model assessment for insulin resistance were significantly higher in patients with AA than in controls.…”
Section: Biomarkersmentioning
confidence: 99%
“…A study including 40 patients with AA and 40 matched controls revealed that the serum levels of interleukin (IL)‐15 in patients were significantly higher than those in the control group and positively correlated with the Severity of Alopecia Tool (SALT) score 8 . A study including 30 patients with AA and 15 matched controls indicated that serum interferon (IFN)‐γ levels were significantly higher in patients than in controls and were significantly correlated with disease activity status and duration 9 . A study including 65 patients with AA and 71 healthy controls demonstrated that serum levels of adiponectin were significantly lower in patients with AA than in controls and were negatively correlated with the SALT score 10 .…”
Section: Progress In Evaluations and Diagnosismentioning
confidence: 99%